ANALISIS TINGKAT KEKRITISAN LAHAN DI KAWASAN REHABILITASI PT. ARUTMIN INDONESIA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Razy, M. Syahrul; Badaruddin, Badaruddin; Kadir, Syarifuddin (Jurnal Hutan Tropis, 2024)
The purpose of this research is to analyze the level of criticality of land in the Riam Kanan Sub-watershed, Banua Riam Village, Aranio District, Banjar Regency as an effort to control the level of criticality of land and reduce the level of flood vulnerability for environmentalsustainability. The data sampling method was determined using a purposive sampling technique, which means the sample points were determined dliberately. The sample points taken are based on land units originating from the land unit map (overlay). Sampling will be carried out in two ways, namely the first way using a soil drill to analyze the structure, soil solum, texture and organic material, while the second way uses a sample ring to determine the permeability at each place. At each point the biophysical parameters were observed in the form of land cover type, slope slope and soil conservation and soil samples were taken for further observations in the soil laboratory. Land Criticality Level (TKL) shows relatively varied classes, namely Somewhat Critical and Potentially Critical. Land cover of PT. Rehabilitation area. Arutmin Indonesia Benua Riam Village, Aranio District, Banjar Regency is a Plantation Forest (HT) with an area of TKL Index 2 (Somewhat Critical) of 13.93 ha (8%), Index 3 (Potentially Critical) of 162.00 ha (92%)